Giant congenital melanocytic nevus: a rare case report - Tyagi, Arty; Kumar, Bipin; Kumar, Mani Kant (International Journal of Contemporary Pediatrics, 2020)
Giant congenital melanocytic nevus is usually defined as a melanocytic lesion present a birth. Its incidence is estimated in <1 in 20,000 newborns. Despite its rarity, this lesion is important because it may be associate with severe complications such as malignant melanoma and may also cause neurological deficit including neurocutaneous melanocytosis. Giant congenital melanocytic nevus generally present as a brown lesion with flat or mammilated surface, well-demarcated borders and hypertrichiosis. Congenital melanocytic nevus is primarily a clinical diagnosis. Recently, we encountered a 3 day old baby girl in whom giant congenital melanocytic nevi was noted at birth. She presented with large nevus over posterior trunk, head and extremities. Magnetic resonance imaging (MRI) brain was normal. Parents were counselled regarding possible future course and were asked to be in regular follow-up. Here, we report this rare case with giant congenital melanocytic nevi.